Implementation of Work Discipline at PT Sumisho Global Logistic in Karawang City - Fachrizal, Peppy (Journal of Management, 2023)
The purpose of this study is to determine the effects of workload, work discipline, and work motivation on the performance of PT Sumisho Global Logistic's sales department personnel in Karawang City, including sales manager supervisors, sales supervisors, managers, and sales officers. In this study, saturated sampling is employed. 101 participants in the study completed the questionnaire, making up the sample. This study used quantitative methods. Descriptive statistical tests, including the validity and reliability test, the influence test (specifically, the multiple linear regression test and the coefficient of determination test), the hypotheses (specifically, the t test and f test), and classic assumptions (such as normality, multicollinearity, and heteroscedasticity) are used in PT Sumisho Global Logistics to analyse data quality. Workload, discipline, and motivation are factors that affect how well corporate sales department staff perform